Features of educational work at present in higher education - Vasilyeva, I. (Problems of Engineer-Pedagogical Education, 2018)
In the article features educational activities at the university, the aims, objectives and principles of educational work in higher education. The article highlighted elements that provide content organization and management structure of educational activities in higher education; quality education is seen as a system characteristic of education; determined by the level of educational activities. The author notes problems with Aborted skills training of graduate schools and ways to overcome them, including the role of coaching institute, which carries out important work to create student groups, promotes regularity and complexity of educational work with students helps prevent deviant behavior of youth. Attention is paid to research the specifics of humanization and humanization of education at the present stage as factors that contribute to the formation of future professionals a more complete picture of the world, which coincides with the general purpose of education and training of cultural rights. Support for the initiative, proactive stance, values students is a real indicator of civilized society, strengthening democratic principles in it.